2019
DOI: 10.1088/1361-6528/ab19d3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field-assisted selective delivery of doxorubicin to cancer cells using magnetoliposomes as drug nanocarriers

Abstract: Magnetoliposomes are promising candidates for the development of selective drug delivery systems in the treatment of cancer. Those nanosystems were tested as carriers of a strong chemotherapeutic agent, doxorubicin, which is used against breast cancer. Herein, the magnetic properties of hydrophobic iron oxide nanoparticles located exclusively in the lipid bilayer were used to release this drug from the magnetoliposomes. The cytotoxic activity of the nanostructures against the normal and cancer cell lines was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…The magnetic properties of hydrophobic IONPs encapsulated exclusively in the lipid bilayer of liposomes were used to release Dox from the MLs. Further, the cell viability results demonstrated that the developed formulation was biocompatible and effective for the treatment of breast cancer [54] . In another study, methotrexate (MTX) loaded thermosensitive MLs were prepared for the target delivery to cervical cancer.…”
Section: Biomedical Application Of Hp-mnpsmentioning
confidence: 90%
“…The magnetic properties of hydrophobic IONPs encapsulated exclusively in the lipid bilayer of liposomes were used to release Dox from the MLs. Further, the cell viability results demonstrated that the developed formulation was biocompatible and effective for the treatment of breast cancer [54] . In another study, methotrexate (MTX) loaded thermosensitive MLs were prepared for the target delivery to cervical cancer.…”
Section: Biomedical Application Of Hp-mnpsmentioning
confidence: 90%
“…The design of nanosystems based on iron oxide NBMs for controlled drug release is another promising area that is being intensively pursued using different approaches, such as drug encapsulation in the polymeric coating layer (Khaledian et al, 2020;Tsai et al, 2020), or by drug co-encapsulation in micelles (Bai et al, 2018;Manigandan et al, 2018), hydrogels (Indulekha et al, 2017;Zou et al, 2020), liposomes (Jose et al, 2019;Szuplewska et al, 2019), lipid NPs (Świętek et al, 2020), polymeric NPs (Mosafer et al, 2017;Luque-Michel et al, 2021), and mesoporous silica nanostructures (Asghar et al, 2020). The stimulated release is a very interesting strategy since it allows a better control on the delivery, ensuring the medicine will be released in the desired site and the therapeutic dose will be achieved (Santhosh and Ulrih, 2013;Monnier et al, 2014).…”
Section: Nanobiomaterials Based On Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Therefore, chemically functionalized maghemite ( γ -Fe 2 O 3 ) is used as an alternative in drug delivery systems targeting tumor cells via material surface modifications [34]. Recently, iron oxides have been conjugated with liposomes to create magnetoliposomes that are able to deliver chemical agents via selective drug release when exposed in a magnetic field [35]. Endeavors to create versatile and reliable delivery systems have led to inorganic carriers composed of carbon or silica-conjugates such as siliciumdioxide.…”
Section: Metallic and Inorganic Particlesmentioning
confidence: 99%